The spiritual foundations of goodness in the works of I. Franko: the noosphere aspect (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article concerns the problems about spiritual aspects of doing good in Ivan Franko's literary works. These are the scientific, mental, spiritual issues as well as the conflict between good and evil. The represented understanding of the Ivan Franko's 'The anthem' is given in the sense of interconnection with the author's ideology of social development and the inner world of a man who is fighting for his spiritual renewal and the national formation in general. The most effective methods and forms of pupil's studying activity have been defined. The noosphere education literary practice emphasizes attention upon the effectiveness of bioadequete methods. The harmonically developed reader is a spiritually rich and creatively active person living in a balanced society and world.
Keywords: key image; cultural; biographical aspect; algorithm; noosphere; image-on; BRC (biological reverse connection) method